Seeing the trees for the forest: Adoption dynamics of the Forest Stewardship Council. Issue 4 (7th April 2022) - Depoorter, Charline; Marx, Axel
Abstract: The integration of voluntary sustainability standards (VSS) into public policy (i.e., their institutionalization) is generally considered a driver for their adoption. However, although the Forest Stewardship Council (FSC), a leading VSS in forest governance, has been increasingly institutionalized, its adoption has been stagnating recently. To understand what drives this stagnation, we analyze the adoption of FSC certification globally and at the country level over a 20‐year period. We show that the global stagnation in FSC adoption hides distinct adoption dynamics at country level. We highlight three types of country‐level adoption dynamics: stagnation, growth, and decline. Based on selected descriptive country case studies, we explore factors driving these dynamics, with a focus on the role of governments and competition with other VSS.